‫‬‬‬‬‬The Role Of Modern Techniques Of Management Accounting and Cost Accounting in Improving Cost Efficiency and Quality Of Care in Urology: a Theoretical Study - Rasha Jasim Ahmed Ebraheem Alobaidy (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
Economic and demographic developments in the past few decades have increased the pressure on efficiency in the healthcare industry. Modern management accounting and cost accounting techniques are a critical component in improving the efficiency and quality of care in urology. With the ever-increasing costs of healthcare, the need for a sophisticated accounting system that can provide accurate data on costs and revenues is more important than ever. The aim of this research was to investigate the role of modern techniques in management accounting and cost accounting as a means of enhancing cost efficiency and quality of care in urology. The research highlights the importance of training medical staff in these techniques, as this can improve overall performance and reduce costs without compromising the quality of care provided to patients. These techniques have been shown to help physicians and administrators make informed decisions, which helps improve the efficiency and quality of care. They also contribute to improving communication between medical teams, enabling better patient care. By focusing on improving resource and cost management, these techniques can play a pivotal role in achieving superior and effective health outcomes.